Relevansi Pencapaian Maqam dalam Tasawuf dengan Insan Kamil - Yosse Oulia Arsyath; Syarifuddin Syarifuddin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Abstract How can you be close and loved if you don't know each other? If you don't know, you won't love, if you don't, you won't love. Likewise, every Muslim community tries to be close to and love Allah SWT. Closeness and love to Allah SWT can only be achieved with perfect Ihsan. And the perfection of Ihsan can only be learned through the science called Sufism. All of its implementation is related to and related to the inner/spiritual. It is with this love that a Muslim happily carries out all commands and stays away from the prohibitions of Allah SWT. Ridha as the highest station must be achieved by every Muslim, who can let go and expel feelings of displeasure from within his heart, so that there are no more feelings other than joy and joy in carrying out the commands and prohibitions of Allah SWT. Humans who perfectly carry out commands and prohibitions are called Insan Kamil. This study of journal to describe and review the relevance of achieving maqam in sufism with insan kamil. This research is library research because the data sources is in the form library materials such as books, journals and scientific articles. In accordance with its type, data collection in this study uses library research methods which are analyzed using the method of description and data analysis. The results of this study indicate that there is a relevance of the achievement of maqam in sufism with insan kamil.